Adhesive protective film, optical member including same, and optical display device including same
By using an adhesive protective film containing a (meth)acrylic copolymer on optical components and adjusting the peel strength before and after light irradiation, the protection needs of polyimide optical devices during processing are solved, a balance between temporary and permanent protection is achieved, and the durability and production efficiency of the device are improved.
Patent Information
- Application Number
- CN202510384430.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-03
- Filing Date
- 2025-03-28
- Publication Date
- 2025-10-17
AI Technical Summary
The existing technology makes it difficult to provide an adhesive protective film that can provide both temporary protection at low peel strength and permanent protection at high peel strength during the processing of optical components, especially for polyimide optical devices containing polyimide ash. In addition, the peel strength does not change sufficiently before and after light irradiation, affecting production efficiency and device durability.
An adhesive protective film composition comprising a (meth)acrylic copolymer, a curing agent, a monofunctional or high-functional monomer containing an aromatic group, and a photoinitiator is used. The peel strength is adjusted before and after light irradiation to ensure that the initial peel strength is less than 7gf/inch and reaches 200gf/inch or higher after light irradiation. The adhesive protective film composition is suitable for polyimide gray surfaces.
It achieves temporary protection at low peel strength and permanent protection at high peel strength during the processing of optical components, avoids scratches and bubbles, and improves the durability and production efficiency of optical devices.
Smart Images

Figure CN120795819A_ABST
Abstract
Description
[0001] CITATION OF RELATED APPLICATION
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2024-0045098, filed on April 3, 2024, in the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference. TECHNICAL FIELD
[0003] The present disclosure relates to an adhesive protective film, an optical member, and an optical display apparatus. BACKGROUND
[0004] In a conventional device, a protective film composed of only an adhesive layer or a protective film composed of a base film and an adhesive layer is attached to the surface of the device in an optical member or an electronic member to prevent scratches thereon during certain processes such as machining, assembly, inspection, etc. Such a protective film is used by removing a release film from the adhesive layer. In recent years, optical members such as organic light emitting diode (OLED) devices are replacing liquid crystal devices. In addition, flexible OLED devices are increasing in the art.
[0005] Unlike liquid crystal devices or typical OLED devices, flexible OLED devices require a process protective film to protect the OLED panel from surface scratches during machining, assembly, inspection, etc. due to its flexibility. The process protective film requires low peeling strength and reworkability as well as the ability to be easily removed during panel inspection when a defect such as an appearance abnormality or a foreign matter is generated. A P-film (patterned film) is permanently attached to the panel to support the panel while protecting the panel from moisture or an external environment after inspection. Since the P-film must be permanently attached to the panel, the P-film requires high peeling strength and reliability.
[0006] Therefore, since the typical panel manufacturing process requires a low peeling strength process protective film for temporary use and a high peeling strength P-film requiring high peeling strength, a process including (i) process protective film attachment; (ii) process protective film removal; and (iii) P-film attachment is required.
[0007] In recent years, cost reduction and process optimization are continuously being pursued. As a result of these continuous efforts, the process protective film is patterned by laser when used as a process protective film before UV irradiation. Here, when the initial peeling strength of the protective film to the polyimide substrate is greater than a certain predetermined degree, productivity can be deteriorated due to a decrease in the peeling success rate. Therefore, there is a need to provide an adhesive protective film having low peeling strength when stacked on a polyimide substrate and exhibiting high peeling strength after UV irradiation in order to incorporate the process protective film into the P-film.
[0008] Background information of the present disclosure can be found in, for example, Japanese Patent Registration No. 5,683,369, and the like. SUMMARY
[0009] An object of the present disclosure is to provide an adhesive protective film that exhibits excellent peeling performance when attached to a polyimide-based optical device having polyimide ash.
[0010] An object of the present disclosure is to provide an adhesive protective film that can be fixed to a polyimide-based optical device having polyimide ash, the adhesive protective film having a large peeling strength after light irradiation than before light irradiation to improve the durability of the optical device.
[0011] An object of the present disclosure is to provide an adhesive protective film that prevents the generation of bubbles when attached to a polyimide-based optical device having polyimide ash.
[0012] An object of the present disclosure is to provide an adhesive protective film that can be used as a temporary protective film for a process on a flexible light emitting device panel substrate, and as a protective film for pattern enhancement that can be selectively peeled to form a pattern.
[0013] One aspect of the present disclosure relates to an adhesive protective film for a polyimide-based optical device containing polyimide ash.
[0014] In one embodiment, the adhesive protective film comprises a cured product of a composition comprising a (meth)acrylic copolymer, a curing agent, a mono-or higher functional monomer containing an aromatic group, and a photoinitiator, wherein the adhesive protective film has an initial peeling strength of 7 gf / inch or less for a polyimide ash-containing surface, and after light irradiation to the adhesive protective film attached to the polyimide ash-containing surface, the adhesive protective film has a peeling strength of 200 gf / inch or more for the polyimide ash-containing surface.
[0015] Another aspect of the present disclosure relates to an adhesive protective film.
[0016] In one embodiment, the adhesive protection film comprises a cured product of a composition comprising a (meth)acrylic copolymer, a curing agent, an aromatic group-containing monofunctional or high-functionality monomer, and a photoinitiator. The adhesive protection film has an initial peel strength of 7 gf / inch or less to a polyimide ash-containing surface configured to be attached thereto, and after light irradiation, the adhesive protection film has a peel strength of 200 gf / inch or more to the polyimide ash-containing surface.
[0017] One aspect of the present disclosure relates to an optical member.
[0018] In one embodiment, the optical member includes a polyimide-based optical device including a polyimide ash-containing surface including a polyimide ash on at least one surface of the polyimide-based optical device, and an adhesive layer layered to the polyimide ash-containing surface. The adhesive layer includes an adhesive protection film.
[0019] In one embodiment, the optical member includes a polyimide-based optical device including a polyimide ash-containing surface including a polyimide ash on at least one surface of the polyimide-based optical device, and an adhesive layer layered to the polyimide ash-containing surface. The adhesive layer includes an adhesive protection film.
[0020] One aspect of the present disclosure relates to an optical display apparatus.
[0021] In one embodiment, the optical display apparatus includes an adhesive protection film or a cured product of an optical member.
[0022] Embodiments of the present disclosure provide an adhesive protection film that exhibits excellent peel performance when attached to a polyimide-based optical device having a polyimide ash.
[0023] Embodiments of the present disclosure provide an adhesive protection film that can be fixed to a polyimide-based optical device having a polyimide ash, the adhesive protection film having a much higher peel strength after light irradiation than before light irradiation to improve durability of the optical device.
[0024] Embodiments of the present disclosure provide an adhesive protection film that prevents the generation of air bubbles when attached to a polyimide-based optical device having a polyimide ash.
[0025] Embodiments of the present disclosure provide an adhesive protection film that can be used as a temporary protection film for a process on a flexible light emitting device panel substrate, and as a protection film for pattern enhancement that can be selectively peeled to form a pattern. BRIEF DESCRIPTION OF DRAWINGS
[0026] Figure 1 is a flowchart illustrating a method of forming a polyimide layer having polyimide blush according to one embodiment of the present disclosure.
[0027] Figure 2 is a flowchart illustrating a method of forming a polyimide layer having polyimide blush according to one embodiment of the present disclosure.
[0028] Figure 3 is a schematic diagram illustrating a laser irradiation process during manufacturing of a polyimide layer having polyimide blush according to one embodiment of the present disclosure.
[0029] Figure 4 is a flowchart illustrating a process of evaluating a peeling performance according to one embodiment of the present disclosure.
[0030] Figure 5 is a cross-sectional view of an optical member according to one embodiment of the present disclosure. DETAILED DESCRIPTION
[0031] Hereinafter, exemplary embodiments of the present disclosure will be described in detail with reference to the accompanying drawings so as to be able to easily carry out the present disclosure by a person having ordinary skill in the art. It should be understood that the present disclosure can be embodied in various ways and is not limited to the following embodiments. In order to facilitate the understanding of the present disclosure, the drawings are not drawn to actual scale, and the size of some components can be exaggerated. Also, the same reference numerals can be assigned to the same components in different embodiments.
[0032] In order to explain the relationship of one element or feature to another element or feature as shown in the drawings, spatial relative terms such as "under", "below", "lower", "on", "upper" and the like can be used herein for ease of description. The spatial relative positions will be understood to include different orientations of the device in use or operation in addition to the orientations depicted in the drawings. For example, if the device in the drawings is turned over, the element described as "under" or "lower" other elements is understood to be "on" or "upper" the other elements. Therefore, the term "under" can include both upward and downward directions.
[0033] The terms used in this document are for the purpose of describing the example embodiments and are not intended to limit the present disclosure. The terms and words used in the specification and claims should not be interpreted as being limited to their ordinary meanings or dictionary meanings. Instead, the terms and words should be interpreted to give the concept of the invention the broadest possible interpretation in accordance with the principles of the inventor(s) in defining the concept of the invention so as to interpret his or her invention in the best possible way, and the terms and words must be interpreted in the meaning and concept consistent with the technical idea of the present disclosure. Since the embodiments described in the specification and the configurations shown in the drawings are only some of the most preferred embodiments and configurations of the present disclosure, they do not represent all technical ideas of the present disclosure, and it should be understood that various equivalents and modified examples of the embodiments are possible.
[0034] As used herein, "comprise", "include" and / or "comprising", "including" mean that existence of the mentioned items, numbers, steps, actions, components, elements and / or groups thereof are present and does not exclude the presence or addition of one or more other items, numbers, operations, components, elements, and / or groups.
[0035] Although first, second, etc. are used to describe various components, it goes without saying that the components are not limited to these terms. These terms are used only to distinguish one component from another component, and unless specifically indicated to the contrary, a first component can also be a second component.
[0036] As used herein, the singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0037] As used herein, "(meth)acryl" means acryl and / or methacryl.
[0038] As used herein, "copolymer" can include a polymer or a resin.
[0039] As used herein, "glass transition temperature" can refer to a glass transition temperature (Tg) measured for a target monomer using a DSC Discovery (TA Instruments). Specifically, a homopolymer of the target monomer is heated to 180℃ at a heating rate of 20℃ / min, slowly cooled to -100℃, and heated again to 100℃ at a heating rate of 10℃ / min to obtain data for an endothermic transition curve. The inflection point of the endothermic transition curve can be defined as the glass transition temperature of the target monomer.
[0040] As used herein, "X to Y" to indicate a specific numerical range means a value greater than or equal to X and less than or equal to Y (i.e., X≤ and ≤Y).
[0041] The adhesive protective film according to the disclosure can be in a certain state before light irradiation and can be provided in the form of an adhesive layer.
[0042] The adhesive protective film can be configured to protect a polyimide-based optical device including a polyimide-dusted surface before light irradiation. In addition, the adhesive protective film can be configured to improve the durability of the polyimide-based optical device after light irradiation. The adhesive protective film can be an adhesive protective film having a peel strength variable by light irradiation.
[0043] Specifically, the adhesive protective film can be attached to the polyimide-dusted surface and configured to temporarily protect the polyimide-dusted surface. Accordingly, the adhesive protective film can be configured to prevent scratches on the polyimide-dusted surface during certain processes such as machining, assembly, inspection, etc. In particular, the adhesive protective film can be attached to the polyimide-dusted surface and can be configured to prevent the generation of air bubbles.
[0044] After the adhesive protective film is attached to the polyimide-dusted surface and is patterned thereon, the adhesive protective film having enhanced peel-off performance can be peeled off from the polyimide-dusted surface and / or the optical device.
[0045] The adhesive protective film can be an adhesive film having a variable peel strength by adjusting light irradiation, and can be adhered to the polyimide-dusted surface with a peel strength greater after light irradiation than before light irradiation, thereby improving the durability of the polyimide-based optical device.
[0046] As used herein, "polyimide-based optical device" refers to a polymer film processed by polymerization from a polyamic acid precursor. The polyimide-based optical device can include imide and aromatic groups in a repeating unit, has excellent mechanical properties and heat resistance, and can be used as a substrate for a flexible OLED panel.
[0047] In one embodiment, the polyimide-based optical device can be provided in the form of a polyimide layer including a polyimide-dusted surface.
[0048] The following describes a method of forming a polyimide layer including a polyimide-dusted surface.
[0049] Figure 1 FIG. 1 is a flowchart illustrating a method 100 of forming a polyimide layer having polyimide dust according to one embodiment of the disclosure.
[0050] Referring to FIG. 1, Figure 1 (1) A polyimide varnish is deposited until a predetermined thickness is satisfied on a lower surface of a glass plate 10 to form a polyimide varnish coating layer 11.
[0051] (2) The polyimide varnish coating 11 is dried and cured to form a polyimide layer 12 on the lower surface of the glass sheet 10.
[0052] (3) The glass sheet 10 is irradiated with a laser beam emitted from a laser irradiator 13 placed above the glass sheet, thereby forming a polyimide ash 14 on the upper surface of the polyimide layer 12.
[0053] The laser irradiation can form the polyimide ash by contacting (e.g., burning) a portion of the polyimide layer. The polyimide ash can refer to, for example, fine irregularities in the form of dust, which can form a fine step between the laser-processed portion and the non-laser-processed portion. The step can contribute to the delamination of the glass sheet in step (4) shown below. The degree of formation of the polyimide ash 14 or the area ratio of the polyimide ash 14 (the ratio of the total area of the polyimide ash to the total area of the polyimide layer) can be adjusted depending on the type of polyimide varnish, the total thickness of the polyimide layer, the degree of irradiation with the laser beam, and the like.
[0054] (4) The glass sheet 10 can be removed from the polyimide layer 12, thereby providing a polyimide layer 15 including a surface containing the polyimide ash 14.
[0055] Figure 2 is a flowchart showing a method 200 of forming a polyimide layer having a polyimide ash according to one embodiment of the present disclosure.
[0056] Referring to Figure 2 , (1) A polyimide varnish is deposited until a predetermined thickness is satisfied on the upper surface of a release base film 16 to form a polyimide varnish coating 11.
[0057] (2) The polyimide varnish coating 11 is dried and cured to form a polyimide layer 12 on the upper surface of the release base film 16.
[0058] (3) The glass sheet 10 is disposed on the upper surface of the polyimide layer 12.
[0059] (4) The glass sheet 10 is irradiated with a laser beam emitted from a laser irradiator 13 placed above the glass sheet, thereby forming a polyimide ash 14 on the upper surface of the polyimide layer 12.
[0060] The laser treatment can form the polyimide ash by contacting (e.g., burning) a portion of the polyimide layer. The polyimide ash can refer to a fine irregularity in the form of dust, which can form a fine step between the laser-treated portion and the non-laser-treated portion. The step can contribute to the glass sheet delamination in step (5) shown below. The degree of formation of the polyimide ash 14 or the area ratio of the polyimide ash 14 (the ratio of the total area of the polyimide ash to the total area of the polyimide layer) can be adjusted depending on the type of the polyimide varnish, the total thickness of the polyimide layer, the degree of irradiation with the laser beam, etc.
[0061] (5) The glass sheet 10 can be removed from the polyimide layer 12, thereby providing a laminate of the polyimide layer 15 having the polyimide ash 14 on the surface thereof and the release base film 16.
[0062] The release base film 16 can be release-treated with silicone or the like, and thus can be easily removed.
[0063] Figure 3 is a schematic diagram illustrating a laser irradiation process 300 during formation of a polyimide layer having a polyimide ash according to one embodiment of the present disclosure.
[0064] Referring to Figure 3 , a laminate is manufactured according to one embodiment of the present disclosure. The polyimide layer 12 and the glass sheet 10 are sequentially stacked on the upper surface of the release base film 16. By using the laser irradiator 13, the laminate is irradiated from above the upper surface of the glass sheet 10 with one or more laser beams 18 to form the polyimide ash 14 on the upper surface of the polyimide layer 12. The laminate is conveyed in a certain direction (toward the left-hand side of Figure 3 , and the polyimide ash 14 can be discontinuously formed on the upper surface of the polyimide layer 12 by intermittent laser irradiation.
[0065] The glass sheet can be an alkali-free glass sheet, and can have a thickness of 1 mm to 2 mm.
[0066] The polyimide varnish can include 90 wt% or more of at least one of a polyimide copolymer, a polyimide oligomer, and a polyimide monomer, but is not limited thereto. For example, the polyimide varnish can include SD Flex (DuPont), but is not limited thereto.
[0067] The polyimide varnish can be deposited by any typical method known to one of ordinary skill in the art. For example, the polyimide varnish can be deposited by a doctor blade coating method. In this method, a gauge can have a diameter of 0.5 mm to 1.0 mm (e.g., 0.65 mm). The polyimide varnish can be deposited to a thickness of up to 20 μm to 30 μm.
[0068] The polyimide varnish coating may be dried and cured to form a polyimide layer.
[0069] Drying may include heat treatment at 50°C to 200°C for 5 to 60 minutes. The heat treatment may be performed once, twice, or more times. In one embodiment, the heat treatment may be performed twice or more. For example, drying may include a first heat treatment at 50°C to 100°C for 5 to 30 minutes and a second heat treatment at 100°C to 200°C for 5 to 30 minutes. Preferably, the first heat treatment is performed at 80°C for 10 minutes, and the second heat treatment is performed at 120°C for 20 minutes.
[0070] The dried product of the polyimide varnish coating may have a thickness of 20 μm to 30 μm, preferably 20 μm.
[0071] Curing can include heat treatment at a temperature higher than that of drying for an extended period of time. This heat treatment can form a polyimide layer by imidization of the dried product of the polyimide varnish coating. The heat treatment can include heat treatment at a temperature greater than 200°C and less than or equal to 400°C for 30 to 120 minutes. In one embodiment, the heat treatment can be performed one or more times. Preferably, curing includes heat treatment at 250°C for 60 minutes.
[0072] The polyimide layer may have a thickness of 20 μm to 30 μm, preferably 20 μm.
[0073] Laser irradiation may include 100 mJ / cm 2 Up to 500mJ / cm 2 (e.g., 150 mJ / cm 2 Up to 200mJ / cm 2 ) dose irradiation. Within this range, the polyimide gray product can be easily peeled off from the glass plate. The laser irradiation may include light irradiation at a wavelength of 308 nm and may occur on a picosecond, nanosecond, or femtosecond time scale.
[0074] An adhesive protective film having enhanced release properties may be attached to and patterned on a polyimide ash-containing surface and then peeled from the polyimide ash-containing surface and / or the optical device.
[0075] As used herein, the "enhanced peeling performance" refers not only to peeling the patterned adhesive protective film without deforming the polyimide-based optical device including the polyimide ash-containing surface or the polyimide ash-containing surface when peeling the patterned adhesive protective film from the polyimide ash-containing surface, but also to selectively peeling only the portion to be peeled at the same time without dragging between the portion to be peeled and the non-portion to be peeled formed by patterning. According to one embodiment, the portion to be peeled and the non-portion to be peeled can be alternately placed.
[0076] Figure 4 is a flowchart showing a process 400 of evaluating the peeling performance.
[0077] Referring to Figure 4 , (1) a laminate is manufactured according to one embodiment of the disclosure. The polyimide layer 15 includes a polyimide ash-containing surface. The polyimide layer 15 and the optical device or optical film 20 are sequentially stacked on the upper surface of the adhesive protective film 30. Although not shown in Figure 4 , the lower surface of the polyimide layer 15 is a polyimide ash-containing surface.
[0078] (2) The adhesive protective film 30 of the laminate is patterned by a predetermined method to form a patterned adhesive protective film 31. By patterning, the patterned adhesive protective film 31 is divided into a non-portion to be peeled 31a and a portion to be peeled 31b.
[0079] (3) The portion to be peeled 31b is peeled from the patterned adhesive protective film 31. According to one embodiment, the portion to be peeled 31b can be peeled by a method known to those skilled in the art.
[0080] (4) At least one surface of the patterned adhesive protective film 31 is irradiated with light to cure the non-portion to be peeled 31a, thereby forming a photocured patterned adhesive protective film 32 on the lower surface of the polyimide layer 15.
[0081] (5) The optical device or optical film 20, the polyimide layer 15 including the polyimide ash-containing surface, and the photocured patterned adhesive protective film 32 are manufactured by cutting.
[0082] The peeling performance refers to the degree that, when the patterned adhesive protective film 30 in (2) and (3) is peeled from the polyimide ash-containing surface, not only the patterned adhesive protective film is peeled without deforming the polyimide ash-containing surface or the polyimide-based optical device including the polyimide ash-containing surface, but also only the portion to be peeled 31b is selectively peeled at the same time without dragging between the portion to be peeled 31b and the non-portion to be peeled 31a. Figure 4 The peeling performance refers to the degree that, when the patterned adhesive protective film 30 in (2) and (3) is peeled from the polyimide ash-containing surface, not only the patterned adhesive protective film is peeled without deforming the polyimide ash-containing surface or the polyimide-based optical device including the polyimide ash-containing surface, but also only the portion to be peeled 31b is selectively peeled at the same time without dragging between the portion to be peeled 31b and the non-portion to be peeled 31a.
[0083] An adhesive protection film according to one embodiment of the present disclosure is described below.
[0084] The adhesive protection film includes a cured product of a composition including a (meth)acrylic copolymer, a curing agent, a monofunctional or a high-functional monomer including an aromatic group, and a photoinitiator, wherein the adhesive protection film can have an initial peel strength of 7 gf / inch or less for a polyimide ash-containing surface, and after the adhesive protection film is attached to the polyimide ash-containing surface and is subjected to light irradiation, the adhesive protection film can have a peel strength of 200 gf / inch or more for the polyimide ash-containing surface.
[0085] The adhesive protection film can have an initial peel strength of 7 gf / inch or less for a polyimide ash-containing surface. Within this range, when the patterned adhesive protection film having enhanced peeling performance is peeled from the polyimide ash-containing surface, the patterned adhesive protection film can be peeled without deforming the polyimide ash-containing surface or a polyimide-based optical device including the polyimide ash-containing surface, and a portion to be peeled can be simultaneously selectively peeled without drag between the portion to be peeled and a non-peeled portion formed by patterning. For example, the adhesive protection film can have an initial peel strength of greater than 0 gf / inch and less than or equal to 7 gf / inch (e.g., 1 gf / inch to 7 gf / inch or 4 gf / inch to 7 gf / inch).
[0086] As used herein, "initial peel strength" refers to a peel strength before irradiation with light.
[0087] After the adhesive protection film is attached to the polyimide ash-containing surface and is subjected to light irradiation, the adhesive protection film has a peel strength of 200 gf / inch or more for the polyimide ash-containing surface. Within this range, a polyimide-based optical device including polyimide ash can exhibit good durability. For example, the adhesive protection film can have a post-irradiation peel strength of 300 gf / inch or more (e.g., 300 gf / inch to 600 gf / inch).
[0088] As used herein, "light irradiation" can include irradiation at a wavelength of 280 nm to 430 nm (specifically, at a wavelength of 350 nm to 390 nm) and at a dose of 1,000 mJ / cm 2 UV irradiation can be performed by at least one of a UV LED, a high-pressure mercury lamp, and a metal halide lamp.
[0089] In one embodiment, the adhesive protective film is an adhesive protective film having an enhanced peeling strength, which exhibits a significant increase in peeling strength after light irradiation compared to before light irradiation. Since the adhesive protective film according to the present disclosure has an increased peeling strength after light irradiation, the adhesive protective film attached to the polyimide-based optical device can provide permanent protection for the polyimide-based optical device after light irradiation. Accordingly, the adhesive protective film according to the present disclosure can provide both temporary protection and permanent protection for the polyimide-based optical device, and can serve as both a temporary protective film for certain processes and an enhanced protective film, thereby achieving process simplification, economic feasibility, and environmental friendliness. The temporary protective film for certain processes can be a film that is temporarily attached to an adherend and then removed therefrom, and can be a film that temporarily protects the polyimide-based optical device. The enhanced protective film can be a film that is permanently attached to the polyimide-based optical device to protect the polyimide-based optical device from the external environment and is not configured to be removed from the polyimide-based optical device.
[0090] The adhesive protective film can serve as an enhanced protective film. The enhanced protective film refers to a protective film stacked on at least one surface of a flexible panel to protect the flexible panel from external impact, etc.
[0091] In one embodiment, the adhesive protective film has a peeling strength increase rate of 65 or more, as calculated according to Equation 1. Within this range, the adhesive protective film can be attached to the polyimide-based optical device with enhanced peeling strength and enhanced reliability after light irradiation, thereby providing an adhesive effect for the polyimide-based optical device.
[0092] < Equation 1 >
[0093] The peeling strength increase rate = P2 / P1,
[0094] wherein P1 is an initial peeling strength of the adhesive protective film for the polyimide-containing ash surface (unit: gf / inch) measured for a sample of the adhesive protective film and the polyimide-based optical device including the polyimide-containing ash surface, and
[0095] P2 is a peeling strength of the adhesive protective film for the polyimide-containing ash surface (unit: gf / inch) after light irradiation of the sample.
[0096] Preferably, the adhesive protective film has a peeling strength increase rate of 65 to 200 or 65 to 100, as calculated according to Equation 1. Within this range, the adhesive protective film can easily ensure the above-mentioned ranges of initial peeling strength and peeling strength after light irradiation.
[0097] The adhesive protection film includes a cured product of a composition including a (meth)acrylic copolymer, a curing agent, an aromatic group-containing monofunctional or high-functionality monomer, and a photoinitiator. The curing agent includes an isocyanate curing agent. The isocyanate curing agent is present in an amount of 6 parts by weight or more with respect to 100 parts by weight of the (meth)acrylic copolymer.
[0098] In one embodiment, the cured product can be a thermally cured product.
[0099] In one embodiment, the adhesive protection film can include the aromatic group-containing monofunctional or high-functionality monomer and the photoinitiator dispersed in a matrix of the adhesive protection film formed by thermal curing of the (meth)acrylic copolymer and the isocyanate curing agent.
[0100] (meth)acrylic copolymer
[0101] The (meth)acrylic copolymer is configured to form a matrix of the adhesive protection film and can be cured by the isocyanate curing agent to secure an initial peeling strength of the adhesive protection film. The (meth)acrylic copolymer can also be configured to improve a modulus and cohesion of the adhesive protection film together with the aromatic group-containing monofunctional or high-functionality monomer after light irradiation.
[0102] The (meth)acrylic copolymer can have a glass transition temperature (Tg) of -10°C or less (specifically, -60°C to -20°C). Within this range, the (meth)acrylic copolymer can be configured to provide wetting (adhesion) to a polyimide-based optical device and an initial peeling strength of the adhesive protection film, and can be configured to increase a peeling strength after light irradiation by suppressing shrinkage of the adhesive protection film by adjusting the glass transition temperature, as compared to an oligomer formed of the monofunctional or high-functionality monomer.
[0103] The (meth)acrylic copolymer can have a weight average molecular weight of 500,000 g / mol or more (specifically, 600,000 g / mol to 1,500,000 g / mol). Within this range, the (meth)acrylic copolymer can be configured to provide wetting (adhesion) to an adherend and an initial peeling strength of the adhesive protection film.
[0104] The (meth)acrylic copolymer can include a copolymer of a monomer mixture including an alkyl group-containing (meth)acrylic monomer and a hydroxyl group-containing (meth)acrylic monomer.
[0105] The alkyl group-containing (meth)acrylic monomer is configured to form a matrix of the adhesive protection film and can include an unsubstituted C1 to C 20 The alkyl group-containing (meth)acrylic monomer is configured to form a matrix of the adhesive protection film and can include an unsubstituted C1 to C 11(meth)acrylate.
[0106] For example, the alkyl group-containing (meth)acryl-based monomer can include at least one of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, and lauryl (meth)acrylate.
[0107] The alkyl group-containing (meth)acryl-based monomer can be present in an amount of 85 to 99.5 mol% (specifically, 90 to 98 mol%, or more specifically, 95 to 99 mol%) of the monomer mixture. Within this range, the alkyl group-containing (meth)acryl-based monomer can effectively provide wettability to the adherend and initial peeling strength of the adhesive protective film.
[0108] The hydroxyl group-containing (meth)acryl-based monomer can be a (meth)acrylate containing at least one hydroxyl group. For example, the hydroxyl group-containing (meth)acrylate can include at least one of 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, hydroxyhexyl (meth)acrylate, 1,4-cyclohexanedimethanol mono(meth)acrylate, 1-chloro-2-hydroxypropyl (meth)acrylate, diethylene glycol mono(meth)acrylate, 1,6-hexanediol mono(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, neopentyl glycol mono(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolethane di(meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 4-hydroxycyclopentyl (meth)acrylate, 4-hydroxycyclohexyl (meth)acrylate, and cyclohexanedimethanol mono(meth)acrylate.
[0109] The hydroxyl group-containing (meth)acryl-based monomer can be present in an amount of 0.1 to 10 mol% (specifically, 0.5 to 10 mol%, 0.5 to 5 mol%, 2 to 10 mol%, or 1 to 5 mol%) of the monomer mixture. Within this range, the hydroxyl group-containing (meth)acryl-based monomer can effectively impart cohesion to the adhesive layer to form the adhesive layer and provide initial peeling strength of the adhesive protective film.
[0110] The monomer mixture can include a (meth)acrylic monomer having a homopolymer glass transition temperature of -80°C to 0°C (specifically, -60°C to -20°C). Within this range, the monomer mixture can be configured to facilitate the preparation of a (meth)acrylic copolymer having a glass transition temperature in the above range.
[0111] In one embodiment, the monomer mixture can include 90 mol% or more, 95 mol% or more, or 95 mol% to 99 mol% of a (meth)acrylic monomer having a homopolymer glass transition temperature of -80°C to 0°C (specifically, -60°C to -20°C). Within this range, the monomer mixture can be configured to easily ensure the effects of the present disclosure. Such a monomer can include n-butyl acrylate or the like.
[0112] In one embodiment, the monomer mixture can be free from a monomer containing an aromatic group. An adhesive protection film prepared from a (meth)acrylic copolymer including a monomer containing an aromatic group cannot achieve the above-mentioned peel strength increase rate of Equation 1.
[0113] In one embodiment, the alkyl-containing (meth)acrylic monomer and the hydroxyl-containing (meth)acrylic monomer can be present in a total amount of 99 mol% or more, 99 mol% to 100 mol%, or 100 mol% of the monomer mixture.
[0114] The (meth)acrylic copolymer can be prepared by polymerization of the monomer mixture by a polymerization method known to those skilled in the art. For example, the (meth)acrylic copolymer can be prepared by adding an initiator to the monomer mixture, followed by copolymer polymerization, for example, suspension polymerization, emulsion polymerization, solution polymerization, or the like. The polymerization can be performed at a temperature of 60°C to 70°C for 4 hours to 8 hours. The initiator can be selected from any typical initiator, including azo-based polymerization initiators; and / or peroxides such as benzoyl peroxide or acetyl peroxide.
[0115] curing agent
[0116] The curing agent can be configured to thermally cure the (meth)acrylic copolymer to form a matrix of the adhesive protection film, and can be configured to provide an initial peel strength to the adhesive protection film.
[0117] The curing agent can include an isocyanate curing agent as a thermal curing agent, in which the isocyanate curing agent is present in an amount of 6 parts by weight or more with respect to 100 parts by weight of the (meth)acrylic copolymer. When the isocyanate curing agent is present in an amount of 6 parts by weight or more, preferably 7 parts by weight or more, the adhesive protection film can ensure high peeling performance. For example, the isocyanate curing agent can be present in an amount of 6 parts by weight to 20 parts by weight, 7 parts by weight to 20 parts by weight, 7 parts by weight to 10 parts by weight, 8 parts by weight to 15 parts by weight, or 8 parts by weight to 10 parts by weight with respect to 100 parts by weight of the (meth)acrylic copolymer.
[0118] The isocyanate curing agent can include a di- or higher functional (specifically, di- to hexa-functional) isocyanate curing agent. In one embodiment, the isocyanate curing agent can include at least one of xylene diisocyanate (XDI) including m-xylene diisocyanate, etc.; methylene bis(phenyl isocyanate) (MDI) including 4,4'-methylene bis(phenyl isocyanate), etc.; naphthalene diisocyanate; toluene diisocyanate; hexamethylene diisocyanate; isophorone diisocyanate; and adducts thereof. For example, the adducts can include a trimethylolpropane adduct of toluene diisocyanate, a trimethylolpropane adduct of hexamethylene diisocyanate, or a trimethylolpropane adduct of isophorone diisocyanate, a trimethylolpropane adduct of xylene diisocyanate, an isocyanurate of toluene diisocyanate, an isocyanurate of hexamethylene diisocyanate, and an isocyanurate of isophorone diisocyanate. The isocyanate curing agent can include at least one of the above compounds.
[0119] The curing agent can further include a metal chelate curing agent.
[0120] In one embodiment, the isocyanate curing agent and the metal chelate curing agent can be present in a weight ratio of 10:1 to 5:1 (isocyanate curing agent:metal chelate curing agent) (e.g., 10:1 to 6:1). Within this range, the adhesive protection film can be configured to ensure enhanced peeling performance.
[0121] The metal chelate curing agent can be any metal chelate curing agent and can include a curing agent containing a metal (e.g., aluminum, titanium, iron, copper, zinc, tin, nickel, antimony, magnesium, vanadium, chromium, zirconium, etc.). For example, the metal chelate curing agent can include at least one of the following: aluminum ethyl acetoacetate diisopropylate, aluminum tris(ethyl acetoacetate), aluminum alkyl acetoacetate diisopropylate, aluminum isopropylate, mono-sec-butoxy aluminum diisopropylate, aluminum-sec-butyrate, aluminum ethylate, tetra-isopropyl titanate, tetra-n-butyl titanate, butyl titanate dimer, acetylacetone titanium, titanium octylene glycolate, titanium tetraacetylacetone, titanium ethyl acetate, titanium polyhydroxystearate, and aluminum acetylacetone.
[0122] The metal chelate curing agent can be present in an amount of 3 parts by weight or less (specifically, 0.001 parts by weight to 1 parts by weight, more specifically, 0.01 parts by weight to 1 parts by weight, and more specifically, 0.1 parts by weight to 1 parts by weight) with respect to 100 parts by weight of the (meth)acrylic copolymer. Within this range, the metal chelate curing agent can be configured to provide an additional effect without impairing the effects of the adhesive protection film according to the present disclosure.
[0123] The curing agent (e.g., a mixture of the isocyanate curing agent and the metal chelate curing agent) can be present in an amount of 8 parts by weight to 20 parts by weight (specifically, 8.5 parts by weight to 15 parts by weight, more specifically, 8.5 parts by weight to 10.5 parts by weight, and more specifically, 8.5 parts by weight to 10 parts by weight) with respect to 100 parts by weight of the (meth)acrylic copolymer. Within this range, the adhesive protection film can be configured to exhibit improved reliability.
[0124] monofunctional or polyfunctional monomer containing an aromatic group
[0125] The monofunctional or high-functionality monomer containing an aromatic group has at least one functional group capable of reacting with the aromatic group and the initiator. As used herein, the aromatic group can refer to a C6 to C 50 monocyclic or polycyclic functional group. For example, the aromatic group can refer to a substituted or unsubstituted benzyl group, phenyl group, biphenyl group, terphenyl group, or naphthyl group, etc. Further, as used herein, the term "functional group" can refer to a vinyl or (meth)acrylate group that can effectively prevent excessive shrinkage of the adhesive protection film upon curing by light irradiation.
[0126] The monofunctional or high-functionality monomer containing an aromatic group can contribute to improving the adhesion of the adhesive protection film to the adherend (e.g., a plastic film having an aromatic group, particularly a polyimide-based film) by increasing the attractive force of the adhesive layer of the adhesive protection film to the adherend via a stacking effect with the π-π bond of the adherend. The aromatic group is a bulky substituent larger than a linear or branched alkyl group, and can be inserted into a network-type cured product (e.g., an interpenetrating polymer network (IPN) structure or a semi-IPN structure) of the (meth)acrylic copolymer and the curing agent prior to light irradiation, thereby contributing to suppressing excessive increase in the initial peeling strength of the adhesive protection film to the adherend.
[0127] The monofunctional or high-functionality monomer containing an aromatic group can be configured to increase the cohesion and / or modulus of the adhesive protection film after light irradiation. Thus, when the adhesive protection film attached to the surface of the adherend is cured by light irradiation, the adhesive protection film is able to be attached to the adherend with enhanced peeling strength, thereby being able to increase the peeling strength of the adhesive protection film.
[0128] It is desirable that the homopolymer glass transition temperature of the monofunctional or high-functionality monomer containing an aromatic group be within a predetermined range from the glass transition temperature of the (meth)acrylic copolymer. Even when the adhesive protection film is cured by light irradiation, this condition increases the peeling strength of the adhesive protection film after light irradiation by suppressing shrinkage of the adhesive protection film. The homopolymer glass transition temperature of the monofunctional or high-functionality monomer containing an aromatic group is higher than the glass transition temperature of the (meth)acrylic copolymer, and the difference therebetween can be 20°C or more, for example, 20°C to 120°C or 40°C to 100°C. Within this range, an increase in the peeling strength of the adhesive protection film after light irradiation can be expected.
[0129] The monofunctional or high-functionality monomer containing an aromatic group can have a homopolymer glass transition temperature of 6°C or more (e.g., 6°C to 50°C). Within this range, the monofunctional or high-functionality monomer containing an aromatic group has a higher glass transition temperature than the (meth)acrylic copolymer, thereby improving the peeling strength of the adhesive protection film after light irradiation by improvement in cohesion.
[0130] The monofunctional or high-functional monomer containing an aromatic group can include a compound represented by Formula 1, but is not limited thereto:
[0131]
[0132] wherein R 1 is hydrogen or methyl, s is an integer of 0 to 10, R 2 is a substituted or unsubstituted C6 to C 50 aryl group, or a substituted or unsubstituted C6 to C 50 aryloxy group, and T is a substituted or unsubstituted C1 to C6 alkylene group or a substituted or unsubstituted C1 to C6 alkyleneoxy group.
[0133] As used herein, "aryloxy" refers to an aryl group attached to an oxy group. The point of attachment to the parent moiety is achieved through the oxy group.
[0134] As used herein, "alkyleneoxy" refers to an alkylene group attached to an oxy group. The point of attachment to the parent moiety is achieved through the oxy group.
[0135] As used herein, "substituted" in the expression "substituted or unsubstituted" means that at least one hydrogen atom of the corresponding functional group is substituted with C1 to C 10 alkyl, C1 to C 10 thioalkyl, C1 to C 10 alkoxy, halogen (F, Cl, Br, or I), C3 to C 10 cycloalkyl, or C6 to C 20 aryl.
[0136] Specifically, R 2may be substituted or unsubstituted phenoxy, benzyl, phenyl, biphenyl, terphenyl, naphthyl, and the like. Specifically, the monofunctional or high-functionality monomer containing aromatic group can include at least one of phenoxy (meth) acrylate, 2-ethylphenoxy (meth) acrylate, benzyl (meth) acrylate, phenyl (meth) acrylate, 2-ethylthiophenyl (meth) acrylate, 2-phenylethyl (meth) acrylate, 3-phenylpropyl (meth) acrylate, 4-phenylbutyl (meth) acrylate, 2-(2-methylphenyl)ethyl (meth) acrylate, 2-(3-methylphenyl)ethyl (meth) acrylate, 2-(4-methylphenyl)ethyl (meth) acrylate, 2-(4-propylphenyl)ethyl (meth) acrylate, 2-(4-(1-methylethyl)phenyl)ethyl (meth) acrylate, 2-(4-methoxyphenyl)ethyl (meth) acrylate, 2-(4-cyclohexylphenyl)ethyl (meth) acrylate, 2-(2-chlorophenyl)ethyl (meth) acrylate, 2-(3-chlorophenyl)ethyl (meth) acrylate, 2-(4-chlorophenyl)ethyl (meth) acrylate, 2-(4-bromophenyl)ethyl (meth) acrylate, 2-(3-phenylphenyl)ethyl (meth) acrylate, o-biphenyl (meth) acrylate, m-biphenyl (meth) acrylate, p-biphenyl (meth) acrylate, 2,6-terphenyl (meth) acrylate, o-terphenyl (meth) acrylate, m-terphenyl (meth) acrylate, p-terphenyl (meth) acrylate, 4-(4-methylphenyl)phenyl (meth) acrylate, 4-(2-methylphenyl)phenyl (meth) acrylate, 2-(4-methylphenyl)phenyl (meth) acrylate, 2-(2-methylphenyl)phenyl (meth) acrylate, 4-(4-ethylphenyl)phenyl (meth) acrylate, 4-(2-ethylphenyl)phenyl (meth) acrylate, 2-(4-ethylphenyl)phenyl (meth) acrylate, 2-(2-ethylphenyl)phenyl (meth) acrylate, and mixtures thereof.
[0137] Preferably, the monofunctional or high-functionality monomer containing aromatic group can include at least one of benzyl (meth) acrylate, ethoxylated phenyl phenyl acetate (phenyl (EO)1 acrylate, phenyl (EO)2 acrylate), ethoxylated phenyl phenol acrylate (o-phenylphenol (EO) acrylate), phenoxy benzyl acrylate, diphenyl phenyl acrylate, and naphthyl acrylate (including 1-naphthyl acrylate), and the like.
[0138] Preferably, the monofunctional or high-functional monomer containing an aromatic group is phenoxybenzyl (meth)acrylate.
[0139] The monofunctional or high-functional monomer containing an aromatic group can be present in an amount of 120 parts by weight or more (for example, 120 parts by weight to 150 parts by weight, specifically, 120 parts by weight to 130 parts by weight) with respect to 100 parts by weight of the (meth)acrylic copolymer. Within this range, the monofunctional or high-functional monomer containing an aromatic group can help increase the peeling strength of the adhesive protection film after light irradiation and can inhibit shrinkage of the adhesive protection film.
[0140] initiator
[0141] The initiator is configured to cure the monofunctional or high-functional monomer containing an aromatic group to allow physical change of the adhesive protection film by light irradiation. The initiator can include at least one selected from a photoradical initiator and a cationic photoinitiator, and can further include a thermal initiator.
[0142] In one embodiment, the initiator can include a photoinitiator having a maximum absorption wavelength within a range of irradiation wavelengths applied during light irradiation. For example, the initiator can have a maximum absorption wavelength within a range of 280 nm to 430 nm. Within this range, the initiator is configured to allow photocuring of the monofunctional or high-functional monomer containing an aromatic group by light irradiation. Specifically, the photoinitiator can include a phosphorus-based initiator, a ketone-based initiator, etc., but is not limited thereto.
[0143] The initiator can be present in an amount of 0.01 parts by weight to 7.5 parts by weight (specifically, 0.03 parts by weight to 4.5 parts by weight) with respect to 100 parts by weight of the (meth)acrylic copolymer. Within this range, the initiator can be configured to ensure uniform curing of the monofunctional or high-functional monomer containing an aromatic group by light irradiation, while preventing deterioration of the transparency of the adhesive protection film due to residual initiator.
[0144] The adhesive composition can further include a curing accelerator.
[0145] The curing accelerator can be configured to further improve the cohesion of the adhesive layer during the curing reaction of the adhesive protection film. The curing accelerator can include a curing accelerator known to one of ordinary skill in the art. The curing accelerator can include a tin-based metal compound, a zinc-based metal compound, an amine-based compound, a titanium-based metal compound, a bismuth-based metal compound, and an aluminum-based metal compound. Among these compounds, a tin-based metal compound is preferably used. For example, the tin-based metal compound can include a tetravalent or divalent organic tin-based compound such as dibutyltin dilaurate, bis-acetylacetonate-dibutyltin, dibutyltin dimaleate, or the like.
[0146] The curing accelerator can be present in an amount of 0.001 parts by weight to 3 parts by weight with respect to 100 parts by weight of the (meth)acrylic copolymer. Within this range, the curing accelerator can be configured to accelerate the curing of the adhesive protection film while improving the cohesion of the adhesive protection film.
[0147] The adhesive composition can further include a silane coupling agent.
[0148] The silane coupling agent can be configured to further increase the peeling strength of the adhesive protection film. The silane coupling agent can include a silane coupling agent known to one of ordinary skill in the art. For example, the silane coupling agent can include an epoxy group-containing silane coupling agent such as glycidyloxypropyltrimethoxysilane, glycidyloxypropylmethyldimethoxysilane, or the like, but is not limited thereto.
[0149] The silane coupling agent can be present in an amount of 0.01 parts by weight to 5 parts by weight with respect to 100 parts by weight of the (meth)acrylic copolymer. Within this range, the silane coupling agent can be configured to further increase the peeling strength of the adhesive protection film.
[0150] The adhesive composition can further include an additive. The additive can include an additive known to one of ordinary skill in the art for an adhesive protection film. For example, the additive can include at least one selected from a pigment, a UV absorber, an antioxidant, a leveling agent, an antistatic agent, a retardant, a catalyst, and a reworking agent, but is not limited thereto.
[0151] The adhesive composition can further include a solvent. The solvent can be configured to increase processability of the adhesive composition to form an adhesive protective film having a thin thickness and a uniform surface. The solvent can include a solvent known to one skilled in the art. For example, the solvent can include methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, toluene, etc., but is not limited thereto. In one embodiment, the adhesive composition can have a solid content of 15 wt% to 40 wt% (specifically, 20 wt% to 30 wt%) based on a solid content of the adhesive protective film. Within this range, the composition can be configured to have good coatability.
[0152] The adhesive protective film can have a haze of 5% or less (specifically, 0.1% to 2%) and a total transmittance of 80% or more (specifically, 85% to 95%) in the visible spectrum (e.g., at a wavelength of 380 nm to 780 nm). Within this range, the adhesive protective film can be configured to have good optical transparency and can be used in an optical display device.
[0153] The adhesive protective film can have an adhesive layer thickness of 200 µm or less (specifically, greater than 0 µm to less than or equal to 100 µm, more specifically, 5 µm to 50 µm). Within this range, the adhesive protective film can be configured to provide a protective effect for a flexible panel.
[0154] The adhesive protective film can further include a base film on one surface thereof.
[0155] The adhesive protective film can further include a release film on the other surface thereof.
[0156] One aspect of the present disclosure relates to an optical member.
[0157] The optical member can include a polyimide-based optical device including a polyimide gray on at least one surface thereof and an adhesive layer attached to the polyimide gray-containing surface. The adhesive layer can include a photocured product of an adhesive protective film.
[0158] In one embodiment, the polyimide-based optical device can be based on a flexible substrate. The flexible substrate can be configured to support an optical device, such as an organic light emitting diode, etc.
[0159] The optical device can be further stacked on at least one surface of the polyimide optical device. Such an optical device can be configured to provide electrical conductivity and / or optical functions to the optical display device, such as light emission, polarization, optical compensation, and display quality improvement. For example, the optical device can include a window film, a window, a polarizing plate, a color filter, a retardation film, an elliptically polarizing film, a reflective polarizing film, an anti-reflection film, a compensation film, a brightness enhancement film, an orientation film, a light diffusion film, a glass anti-shatter film, a surface protection film, an OLED device barrier layer, a plastic LCD substrate, and a transparent electrode film (including indium tin oxide (ITO), fluorinated tin oxide (FTO), aluminum-doped zinc oxide (AZO), carbon nanotubes (CNT), Ag nanowires, or graphene, etc.).
[0160] The adhesive layer may include a photocured product of the adhesive protective film.The adhesive layer may be substantially the same as the adhesive protective film.
[0161] In one embodiment, the adhesive layer may be patterned.
[0162] A protective layer may be further stacked on at least one surface of the adhesive layer.
[0163] The protective layer may be configured to protect an adhesive layer or a polyimide-based optical device. The protective layer is not limited to a specific type, as long as the protective layer is optically transparent and can provide flexibility. For example, the protective layer may include a polyester film, such as a polyethylene terephthalate film, a polyethylene naphthalate film, a polycarbonate film, a polyethersulfone film, or the like.
[0164] Figure 5 is a cross-sectional view of an optical member 500 according to one embodiment. Figure 5 The optical component 500 may include a polyimide layer (polyimide-based optical device) 15 having polyimide gray on its lower surface, an optical device or optical film 20 formed on the upper surface of the polyimide layer (polyimide-based optical device) 15 having polyimide gray on its lower surface, and an adhesive layer 33 formed on the lower surface of the polyimide layer (polyimide-based optical device) 15 having polyimide gray on its lower surface.
[0165] One aspect of the present disclosure relates to an optical display device.
[0166] The optical display device may include a cured product of the adhesive protective film or the optical member. The cured product may be a photocured product.
[0167] The optical display device may include an organic light emitting diode display, a liquid crystal display, etc. The optical display device may include a flexible display device. The optical display device may also include a non-flexible display device.
[0168] Example
[0169] The present disclosure will be described in greater detail with reference to the following examples. However, it should be understood that these examples are provided only for illustrating the present disclosure and should not be construed in any manner as limiting the present disclosure.
[0170] Preparation Example
[0171] A solvent (ethyl acetate) was added to a 1L reactor provided with a cooling device to facilitate temperature control under a nitrogen atmosphere. 100 parts by weight of a monomer mixture containing 97 mol% of n-butyl acrylate (homopolymer glass transition temperature: -45°C) and 3 mol% of 4-hydroxybutyl acrylate was added to the reactor. Nitrogen was added to the monomer mixture for 30 min to remove oxygen and the temperature of the reactor was maintained at 62°C. While homogeneously stirring the monomer mixture, 0.07 wt% of an initiator (azobisisobutyronitrile) was added to the monomer mixture and reacted at 62°C for 8 hours to prepare a (meth)acrylic copolymer (weight average molecular weight: 1,000,000 g / mol). A (meth)acrylic copolymer solution (24 wt% in solid content) was prepared by adding ethyl acetate as a solvent to the resulting product.
[0172] Example 1
[0173] An adhesive composition (25 wt%) was prepared by adding TD-75 (isocyanate curing agent, isocyanate reaction type, 75 wt%, Soken Co., Ltd.) and BXX-4805 (aluminum chelate curing agent, 5 wt%, Samyoung Ink Co., Ltd.) as curing agents, phenoxybenzyl acrylate (homopolymer glass transition temperature: 6°C, Hannong Chemical Co., Ltd.) as an aromatic group-containing monofunctional monomer, and Irgacure TPO (phosphorescent initiator, BASF) as a photoinitiator in the amounts listed in Table 1 to 100 parts by weight of the (meth)acrylic copolymer prepared in the preparation example, followed by diluting the resulting solution in methyl ethyl ketone in solid content.
[0174] The prepared adhesive composition was deposited on the antistatic layer-coated surface of a base film (polyethylene terephthalate (PET) film, T914J75, thickness: 75 µm, in which an antistatic layer is coated on one surface, MCC) to a thickness of 13 µm and dried at 110°C for 4 min to form an adhesive layer. Then, a release film (thickness: 25 µm, in which one surface is subjected to silicone release treatment, MHF25, MCC) was laminated to the adhesive layer and left at 50°C for 3 days, thereby preparing an adhesive-protected film-containing sheet in which an adhesive-protecting film (thickness: 13 µm) and a release film are sequentially stacked on a base film.
[0175] Examples 2 to 4
[0176] A sheet containing an adhesive protection film was prepared in the same manner as in Example 1, except that the type and / or content of each component in Example 1 were changed as shown in Table 1.
[0177] Comparative Examples 1 to 5
[0178] A sheet containing an adhesive protection film was prepared in the same manner as in Example 1, except that the type and / or content of each component in Example 1 were changed as shown in Table 1.
[0179] The following properties of the sheet containing an adhesive protection film prepared in the Examples and Comparative Examples were evaluated, and the evaluation results are shown in Table 1.
[0180] Reference Example: Preparation of a polyimide layer having a polyimide gray on one surface
[0181] A polyimide layer having a polyimide gray on one surface was prepared.
[0182] A polyimide varnish (SD Flex, DuPont) was deposited to a thickness of 20 pm onto the upper surface of an alkali-free glass plate (thickness: 1.1 mm) using a doctor blade coating device (gauge diameter: 0.65 mm) to prepare a polyimide varnish coating layer.
[0183] The polyimide varnish coating layer was subjected to heat treatment at 80°C for 10 min and heat treatment at 120°C for 20 min to prepare a dry film of the polyimide varnish coating layer (thickness: 20 pm).
[0184] A laminate of a polyimide layer (thickness: 20 pm) and a glass plate was prepared by curing the dry polyimide varnish layer in a chamber at 250°C for 60 min.
[0185] The laminated stack was irradiated with a laser beam while moving a laser irradiation device (MicroLAS, COHERENT) placed above the glass plate of the laminated stack from one side to the other side. The laser irradiation was performed under the following conditions: wavelength: 308 nm; femtosecond; dose: 170 mJ / cm 2 .
[0186] A polyimide layer having a polyimide gray on one surface was prepared by removing the glass plate after placing the laminated stack at room temperature for 1 hour.
[0187] (1) Initial peel strength (unit: gf / inch):
[0188] The release film was peeled off from each of the adhesive protection film-containing sheets of Examples and Comparative Examples to expose the adhesive protection film. The exposed surface of the adhesive protection film was attached to the polyimide ash-containing surface of the polyimide layer. Then, a sample was prepared by pressing the attached product under a 2-kg load roller and cutting the pressed product into a size of 25 mm x 100 mm (width x length).
[0189] The sample was left to stand at 23°C and 50% RH (relative humidity) for 30 min. According to JIS Z2037, under conditions of a peeling temperature: 25°C, a peeling speed: 2,400 mm / min, and a peeling angle: 180°, the peeling strength of the adhesive protection film was measured when the adhesive protection film was peeled from the polyimide ash-containing surface, using a tensile tester (Texture Analyzer, TA Industry) by a peeling strength measurement method.
[0190] (2) Peeling strength after UV irradiation (unit: gf / inch):
[0191] A sample was prepared in the same manner as in (1).
[0192] The sample was left to stand at 23°C and 50% RH for 30 min. The sample was irradiated with UV light at a dose of 1,000 mJ / cm 2 at a wavelength of 385 nm on the PET film side using a UV LED irradiator (SUV-L5160A, UVSMT), and then left to stand at 23°C and 50% RH for 30 min. According to JIS Z2037, under conditions of a peeling temperature: 25°C, a peeling speed: 2,400 mm / min, and a peeling angle: 180°, the peeling strength of the adhesive protection film was measured when the adhesive protection film was peeled from the polyimide ash-containing surface, using a tensile tester (Texture Analyzer, TA Industry) by a peeling strength measurement method.
[0193] (3) Peeling performance (unit: %):
[0194] The release film was peeled off from each of the adhesive protection film-containing sheets of Examples and Comparative Examples to expose the adhesive protection film. The exposed surface of the adhesive protection film was attached to the polyimide ash-containing surface of the polyimide layer. Then, a sample was prepared by pressing the attached product under a 2-kg load roller and cutting the pressed product into a size of 100 mm x 100 mm (width x length).
[0195] In the sample, the adhesive protection film was patterned by laser irradiation. The patterning was performed by irradiating the adhesive protection film with a laser beam at intervals of 1 cm in both the longitudinal and transverse directions of the adhesive protection film. Then, when the adhesive protection film was partially removed by an adhesive tape or tweezers, the number of pieces simultaneously selectively peeled off without deformation of the surface or polyimide layer containing polyimide ash and without drag between the pieces to be peeled and the pieces not to be peeled was counted. The larger the numerical value, the better the peeling performance.
[0196] (4) Durability after light irradiation:
[0197] The release film was peeled off from each of the adhesive protection film-containing sheet of the examples and comparative examples to expose the adhesive protection film. The exposed surface of the adhesive protection film was attached to the polyimide ash-containing surface of the polyimide layer. The attached product was pressed under a 2 kg load roller and cut into a size of 150 mm x 90 mm (length x width). Then, the pressed product was left at 23°C and 50% RH for 30 min, and then a pressure was applied thereto. The resulting product was irradiated with UV light at a dose of 1,000 mJ / cm2on the PET film side and at a wavelength of 365 nm using a UV LED irradiator (SUV-L5160A, UVSMT), and left at 23°C and 50% RH for 30 min, thereby preparing a sample. 2
[0198] The heat resistance and humidity resistance of the prepared sample were evaluated. After the sample was left at a temperature of 85°C for 500 hours, the heat resistance was evaluated by observing the occurrence of bubbles or delamination. After the sample was left at a temperature of 60°C and 95% RH for 500 hours, the humidity resistance was evaluated by observing the occurrence of bubbles or delamination. The evaluation criteria are shown below. The occurrence of bubbles or delamination between the adhesive protection film and the polyimide ash-containing surface was evaluated with the naked eye.
[0199] : No bubbles or spots
[0200] : 1 bubble or spot
[0201] : Two or three bubbles or spots
[0202] : More than 3 bubbles or spots
[0203] (5) Bubble generation when attached to a polyimide layer
[0204] The release film was peeled off from each of the adhesive protective film-containing sheets of Examples and Comparative Examples to expose the adhesive protective film. The exposed surface of the adhesive protective film was attached to the polyimide ash-containing surface of the polyimide layer. The generation of bubbles or delamination between the adhesive protective film and the polyimide ash-containing surface was evaluated with the naked eye. No bubble evaluation was "good", and the presence of bubbles was "poor".
[0205] Table 1
[0206]
[0207]
[0208] As shown in Table 1, the adhesive protective film according to the present disclosure exhibited excellent peeling performance when attached to a polyimide-based optical device. The adhesive protective film according to the present disclosure can be fixed to a polyimide-based optical device having polyimide ash with a peeling strength after light irradiation that is greater than that before light irradiation, thereby improving the durability of the optical device. The adhesive protective film according to the present disclosure can be configured to prevent the generation of bubbles when attached to a polyimide-based optical device having polyimide ash. The adhesive protective film according to the present disclosure can serve as both a temporary protective film for a process on a flexible light-emitting device panel substrate and a protective film for pattern enhancement that can be selectively peeled to form a pattern.
[0209] It should be understood that various modifications, changes, alterations and equivalents can be made by those skilled in the art without departing from the spirit and scope of the present disclosure.
Claims
1. An adhesive protective film comprising a cured product of a composition comprising: (Meth)acrylic acid copolymers; Curing agent; Monofunctional or high-functional monomers containing aromatic groups; and Photoinitiator, in, The adhesive protective film has an initial peel strength of 7 gf / inch or less with respect to a polyimide ash-containing surface to which it is configured to be attached, and wherein, after light irradiation, the adhesive protective film has a peel strength of 200 gf / inch or more with respect to the polyimide ash-containing surface.
2. The adhesive protective film according to claim 1, wherein The curing agent includes an isocyanate curing agent, wherein the isocyanate curing agent is present in an amount of 6 parts by weight or more relative to 100 parts by weight of the (meth)acrylic copolymer.
3. The adhesive protective film according to claim 2, wherein The curing agent also includes a metal chelate curing agent.
4. The adhesive protective film according to claim 3, wherein The isocyanate curing agent and the metal chelate curing agent are present in a weight ratio of 10:1 to 5:
1.
5. The adhesive protective film according to claim 1, wherein The aromatic group-containing monofunctional or high-functional monomer is present in an amount of 120 parts by weight or more relative to 100 parts by weight of the (meth)acrylic copolymer. The adhesive protective film according to claim 1 , wherein The aromatic group-containing monofunctional or high-functional monomer has a homopolymer glass transition temperature of 6° C. or higher.
7. The adhesive protective film according to claim 1, wherein The monofunctional or high-functional monomer containing an aromatic group includes a compound represented by Formula 1: in R 1 is hydrogen or methyl, s is an integer from 0 to 10, R 2 is substituted or unsubstituted C6 to C 50 Aryl or substituted or unsubstituted C6 to C 50 aryloxy, and T is a substituted or unsubstituted C1 to C6 alkylene group or a substituted or unsubstituted C1 to C6 alkyleneoxy group.
8. The adhesive protective film according to claim 1, wherein The (meth)acrylic copolymer includes a copolymer of a monomer mixture including an alkyl group-containing (meth)acrylic monomer and a hydroxyl group-containing (meth)acrylic monomer.
9. The adhesive protective film according to claim 8, wherein The monomer mixture includes 90 mol % or more of the (meth)acrylic monomer, wherein the (meth)acrylic monomer has a homopolymer glass transition temperature of -80°C to 0°C.
10. The adhesive protective film according to claim 1, wherein The composition includes 100 parts by weight of the (meth)acrylic copolymer, 8 to 20 parts by weight of the curing agent, 120 parts by weight or more of the aromatic group-containing monofunctional or high-functional monomer, and 0.01 to 7.5 parts by weight of the photoinitiator.
11. The adhesive protective film according to claim 1, wherein The adhesive protective film has a peel strength increase rate of 65 or greater calculated according to Equation 1: Equation 1 Peel strength increase rate = P2 / P1, Wherein, P1 is the initial peel strength, in gf / inch, and P2 is the peel strength of the adhesive protective film to the surface containing polyimide gray after light irradiation, unit: gf / inch.
12. An optical component comprising: A polyimide-based optical device, comprising: a surface containing polyimide ash, wherein the surface containing polyimide ash comprises polyimide ash on at least one surface of the polyimide-based optical device; and an adhesive layer laminated to the polyimide ash-containing surface, The adhesive layer comprises the adhesive protective film according to any one of claims 1 to 11. 13 . An optical display device comprising the optical member according to claim 12 .
Citation Information
Patent Citations
Pendulum type play tool to which series weight is attached
JP1981083369A
Aerosol generating device, heating method and computer readable storage medium
KR1020240045098A